Forage yield of cutting grass and effect on compositional quality and yield of milk in a dry Caribbean (2012)
Seasonal climates affect the supply of nutrients in livestock systems. In search of different strategies for feeding livestock, we evaluated the effect of nitrogen fertilization of four cut grasses on yield and feed quality in dual purpose cows in Valle del Cesar. Two phases were developed, the first was the assessment of the performance and quality of feed, where the data were analyzed by a randomized block design with a factorial arrangement of four grasses and five nitrogen sources, the second phase evaluated the animal response, supplying feed based on results in the first phase, using a change-over experimental design. Eight dual purpose cows in the second third of lactation with a weight (W) of 395 kg about were used. The study was conducted at the Motilonia Experimental Station. The type of pasture significantly affected the value for dry matter, being highest in Elefante grass (17.9%) and lowest in morado King-grass (13.3%); feed yield was affected by both fertilization and pasture, being highest in the application of urea and in partnership with Leucaena sp. (12.9 and 12.7 t ha-1, respectively). Fertilization had no effect on the chemical composition of the grasses. We obtained a higher milk production when silage of Elefante grass + Leucaena sp. and Elefante alone (3.98 ± 0.18 and 3.81 ± 0.18 L/cow/day) were supplied, compared to feed without silage. The compositional quality of the milk was positively affected by the silage.